Ultrasonographie quantitative osseuse des phalanges chez des volleyeurs professionnels - El Hage, R.; Jacob, E.; Moussa, E.; Jaffre, C. (Science & Sports, 2010)
Introduction Regular volleyball practice is known to enhance bone mass acquisition. Quantitative ultrasonometry of bone is a noninvasive method which provides information on bone biomechanical properties. The aim of this study was to compare phalange ultrasound variables between adult volleyball players and adult sedentary subjects.